2021
DOI: 10.3846/bmee.2021.13588
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Volatility Spillovers, Cross-Market Correlation and Co-Movements Between Stock Markets in European Union: An Empirical Case Study

Abstract: Purpose – This article examines volatility spillovers, cross-market correlation, and comovements between selected developed and former communist emerging stock markets in the European Union. Modelling the behavioural dynamics of European stock markets represents a vital topic in a fascinating context, but also a current challenge of great interest. Research Methodology – We propose to estimate and model volatility using GARCH family models for selected European markets. We aim to explore volatility movement, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…e output supports that world stock exchange indices influence the Ukrainian index. According to [39], they examined the volatility, crossmarket correlation, and co-movements between developed (Spain, the UK, Germany, and France) and emerging (Poland, Hungary, Croatia, and Romania) stock markets in the European Union. e findings show significant existence of volatility clustering among all the eight markets except for Croatia and Poland.…”
Section: Integrations Between International Financial Markets and Dom...mentioning
confidence: 99%
“…e output supports that world stock exchange indices influence the Ukrainian index. According to [39], they examined the volatility, crossmarket correlation, and co-movements between developed (Spain, the UK, Germany, and France) and emerging (Poland, Hungary, Croatia, and Romania) stock markets in the European Union. e findings show significant existence of volatility clustering among all the eight markets except for Croatia and Poland.…”
Section: Integrations Between International Financial Markets and Dom...mentioning
confidence: 99%
“…According to the basic modern portfolio theory, investing in various types of securities reduces risk. The idea of portfolio diversification was expanded on by Das et al (2018) who advocated an approach that diversifies the portfolio by including foreign markets with a low correlation (Paramati et al, 2016;Trivedi et al, 2021). A number of international financial markets have been investigated in recent years by researchers These studies showed that there were a wide range of relationships between foreign stock markets (Nguyen & Lam, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They show that financial contagion has been identified on these markets between 1998 and 2014, but the process is stronger during crisis periods. Trivedi et al (2021) and Spulbar et al (2020) also study the evolution of comovements for a selected number of developed and emerging markets (8 and 12, respectively). However, they employ a different approach, based on the GARCH family models which investigate the presence of the leverage effect.…”
Section: Literature Reviewmentioning
confidence: 99%